PROSES DAN KAIDAH FONOLOGIS BAHASA BALI DI LINGKUNGAN BABAKAN, LOMBOK BARAT - Susanti, Ni Wayan Pratiwi Mei (Prosiding Seminar Nasional Bahasa Ibu, 2025)
This study analyzes the phonological processes in the Balinese language in Babakan, West Lombok, using the introspective method, which involves observation and data analysis conducted by the researcher as a native speaker of the language. The focus of the research includes phenomena such as assimilation, dissimilation, and addition occurring in the Balinese language in Babakan, West Lombok. The collected data were analyzed using the Determinant Element Sorting (PUP) technique, and the analysis results were presented using formal and informal methods. The findings reveal that each phonological process reflects the language system's efforts to achieve efficiency in pronunciation. The assimilation process demonstrates the influence of adjacent sounds, dissimilation reflects adaptation for smoother articulation and showcases the flexibility of sound patterns. The addition of sounds emerges as a common phenomenon in the Balinese language in Babakan, West Lombok.